Endogenous knowledge on four leafy vegetables used by rural populations in Benin - Sossa-Vihotogbé, Carole Nadia Adjouavi; Anihouvi, Victor B.; AKISSOE, H. NOËL; HOUNHOUIGAN, DJIDJOHO JOSEPH; ahohuend, BONAVENTURE COHOVI; AHANCHEDE, ADAM; SANNI, AMBALIOU (My University, 2012)
Leafy vegetables are sources of diet diversification and could contribute to food and nutritional security in African rural areas. However, in some places, little is known about if, how, and why leafy vegetables are consumed. Processing and preservation methods, food forms, and consumption determinants of four leafy vegetables ( Sesamum radiatum, Ceratotheca sesamoïdes, Acmella uliginosa and Justicia tenella), known to contribute to the diet of rural populations in the Center and Northern parts of Benin, were investigated. Three hundred randomly selected households were investigated, using rapid appraisal and quantitative survey methods, descriptive statistics and correspondence analysis. Processing methods to prepare sauces varied depending on sociocultural groups. Cooking of fresh leaves predominated, while sun drying was the usual practice of preserving these leafy vegetables. Consumption frequencies were associated with sociocultural groups, food habits, and availability in living areas
Keywords: Sesamum radiatum; Ceratotheca sesamoïdes; Acmella uliginosa; Justicia tenella; consumption frequency; processing